2009
DOI: 10.1097/opx.0b013e3181940655
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetics of Human Myopia: An Update

Abstract: Myopia, or nearsightedness, is the most common human eye disorder in the world, and is a significant global public health concern. Along with cataract, macular degeneration, infectious disease, and vitamin A deficiency, myopia is one of the most important causes of visual impairment worldwide. Severe or high-grade myopia is a leading cause of blindness because of its associated ocular morbidities of retinal detachment, macular choroidal degeneration, premature cataract, and glaucoma. Ample evidence documents t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(56 citation statements)
references
References 122 publications
0
56
0
Order By: Relevance
“…Two independent research groups, using genome-wide association studies, have identified 20 genetic loci that have been linked to myopia [7]. Environmental factors such as long periods of near work, type of optical correction, and limited outdoor time also affect myopia development [8][9][10][11]. One study reported that increasing time spent outdoors can delay the onset of myopia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Two independent research groups, using genome-wide association studies, have identified 20 genetic loci that have been linked to myopia [7]. Environmental factors such as long periods of near work, type of optical correction, and limited outdoor time also affect myopia development [8][9][10][11]. One study reported that increasing time spent outdoors can delay the onset of myopia [12].…”
Section: Introductionmentioning
confidence: 99%
“…Myopia is a complex disease resulting from the interaction of multiple genetic and environmental factors [1][2][3]. The incidence of myopia increased dramatically over the last decades; moreover the prevalence of HM (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic studies associated growth factors such as Transforming Growth Factor (TGF-beta), Insulin-like Growth Factor (IGF) or Vascular Endothelial Growth Factor (VEGF) with myopia and HM. The increasing prevalence of the disease is thought however to be driven by environmental factors such as light levels, life style or diet [3,4]. Light levels are inversely associated with myopia progression and this is mainly associated with the release of retinal dopamine, a potent regulator of eye growth.…”
Section: Introductionmentioning
confidence: 99%
“…In a large number of studies, children with myopic parents are more likely to have myopia than those without myopic parents (Guggenheim, Kirov, & Hodson, 2000;Mutti et al, 2002;Mutti & Zadnik, 1995;Saw, Nieto, et al, 2001; M. M. Wu & Edwards, 1999;Young, 2009). The relationship between parents and children might reflect the shared environments as well as the shared genes with respect to refractive error.…”
Section: Risk Factors Related To the Refractive Errormentioning
confidence: 99%